Seasonal changes in nematode faecal egg counts of sheep in Ethiopia - Bekele, T.; Mukasa-Mugerwa, E.; Scholtens, R.G. (1987)
Describes the seasonal pattern of nematode faecal egg counts of sheep slaughtered at the Addis Ababa abattoir from July 1985 to June 1986. Presents data on strongyle and trichostrongyle faecal egg counts. Suggests possible strategic measures for th econtrol of gastrointestinal nematodes of sheep in central Ethiopia.